2023
DOI: 10.1021/acsanm.3c00467
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behaviors of Small Molecules on Two-Dimensional Penta-NiN2 Layers: Implications for NO and NO2 Gas Sensors

Abstract: Penta-NiN 2 is a two-dimensional layered material with pentagonal atomic arrangement and has recently been manufactured in experiments (ACS Nano 2021, 15, 8, 13539). We study systematically the adsorption of CO, CO 2 , NO, NO 2 , NH 3 , and CH 4 on penta-NiN 2 nanosheet and its effects on electronic properties employing the first-principles method combined with the nonequilibrium Green's function. Excellent sensing performance of penta-NiN 2 is predicted for the NO x (x = 1, 2) molecules based on energetic, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that 2D materials with pentagonal structures are good gas−sensitive materials, such as penta−graphene [ 50 ], penta−BCN [ 51 ], and penta−BeP 2 [ 52 ]. On the other hand, penta−NiN 2 [ 21 ] and penta−PdAs 2 [ 27 ], which belong to the same family as the penta−NiPN proposed in this work, have proved to be very good gas−sensitive materials as well. Therefore, we believe that the gas−sensitive properties of the penta−NiPN monolayer are worth exploring.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have shown that 2D materials with pentagonal structures are good gas−sensitive materials, such as penta−graphene [ 50 ], penta−BCN [ 51 ], and penta−BeP 2 [ 52 ]. On the other hand, penta−NiN 2 [ 21 ] and penta−PdAs 2 [ 27 ], which belong to the same family as the penta−NiPN proposed in this work, have proved to be very good gas−sensitive materials as well. Therefore, we believe that the gas−sensitive properties of the penta−NiPN monolayer are worth exploring.…”
Section: Resultsmentioning
confidence: 86%
“…Regarding the adsorption distances, the values ranged from 1.834 Å (CO) to 3.117 Å (N 2 ). The adsorption distances for NO and NO 2 are 1.862 Å and 2.065 Å, respectively, which are shorter than the values observed for NO and NO 2 absorption on the penta−NiN 2 monolayer (2.190 Å and 2.124 Å) [ 21 ]. Adsorption energy and distance can characterize the strength or weakness of interactions between gas molecules and host materials.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent years, researchers have been seeking different gas-sensing materials theoretically and experimentally for improving the selectivity and sensitivity of gas sensors. Traditional metal oxide sensors have disadvantages such as poor selectivity, high energy consumption, and unfriendly to the environment. , The two-dimensional materials are naturally characterized by large areas, ultrahigh carrier mobilities, and rich surface active sites and have attracted great interest. The application of two-dimensional materials in gas sensors may make up for the shortcomings of traditional metal oxide sensors and promote greatly the development of gas sensors. Graphene, silicene, phosphorene, and MoS 2 have been studied for their gas-sensing properties, and some prospective results have been obtained. However, the adsorption of some typical gases, such as CO and CO 2 on those materials is weak, and the interactions between their surfaces and various gases are usually not enough to ensure stable adsorption conditions. To handle this issue, methods like doping other atoms, introducing defects in suitable locations, molecular group functionalizing, and other modification techniques have been proposed. Transition metal (TM) doping is one of the most widely used methods in gas sensing technology.…”
Section: Introductionmentioning
confidence: 99%
“…14 Li et al conducted research on the adsorption of small molecules on a penta-NiN 2 nanosheet and investigated its impact on electronic characteristics. 15…”
Section: Introductionmentioning
confidence: 99%